Survival outcomes in myelofibrosis patients treated with ruxolitinib: A population‐based cohort study in Sweden and Norway. (4th October 2019) - Schain, Frida; Vago, Emese; Song, Ci; He, Jianming; Liwing, Johan; Löfgren, Christina; Björkholm, Magnus
Abstract: Objective: To estimate survival in Swedish and Norwegian myelofibrosis (MF) patients who received ruxolitinib. Methods: Swedish and Norwegian patients with MF diagnosis in the National Cancer Registries (Sweden: 2001‐2015; Norway: 2002‐2016) and ≥1 record of ruxolitinib in the Prescribed Drug Registries (2013‐2017) were included. Patients were followed from ruxolitinib initiation until death or end of follow‐up; those who discontinued ruxolitinib were followed from ruxolitinib discontinuation. Relative survival (RS) and excess mortality rate ratios (EMRRs) were calculated vs a matched general population. Average loss in life expectancy (LEL) was predicted using flexible parametric models. Results: Among patients who initiated ruxolitinib (n = 190), 1‐ and 4‐year RS were 0.80 (95% confidence interval [CI]: 0.74, 0.86) and 0.52 (95% CI: 0.42, 0.64), respectively, and LEL was 11 years. EMRR was greater in patients aged >70 vs <60 years (3.16; 95% CI: 1.34‐7.40). Among patients who discontinued ruxolitinib (n = 71), median RS was 16.0 months (95% CI: 6.3, NE), and LEL was 12 years. After ruxolitinib treatment discontinuation, Swedish patients (n = 37) received glucocorticoids, hydroxyurea, busulfan, danazol and lenalidomide. Conclusion: Swedish and Norwegian MF patients who discontinued ruxolitinib had dismal survival outcomes and limited subsequent treatment options, highlighting the need for improved therapies.